2016
DOI: 10.1002/ange.201608567
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Breaking Charge Transfer and Hydrogen Bonding: Toward Asymmetrical Photochemistry

Abstract: Symmetry-breaking charge transfer upon photoexcitation of al inear A-p-D-p-A molecule (D and Ab eing electron donating and accepting groups) could be visualized using ultrafast time-resolved infrared spectroscopyb ym onitoring the CN stretching modes on the Aunits.W hereas in apolar solvents,the S 1 state remains symmetric and quadrupolar,s ymmetry breaking occurs within ca. 100 fs in polar solvents as shown by the presence of two CN bands,instead of one in apolar solvents,w ith as plitting that increases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
2
40
1
Order By: Relevance
“…This model predicts complete exciton localization even in weakly polar media (D = 0.985 in benzene and D = 0.993 in chloroform, with D = 1 being a full localization on a single branch). This result differs from previous investigations, where complete localization was only achieved in the most polar solvents 30,34 , or could not be realized at all 32,33 . It is possible here because of the weak electronic coupling between the branches (~850-900 cm −1 ) and the large charge transfer in each arm upon photoexcitation.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This model predicts complete exciton localization even in weakly polar media (D = 0.985 in benzene and D = 0.993 in chloroform, with D = 1 being a full localization on a single branch). This result differs from previous investigations, where complete localization was only achieved in the most polar solvents 30,34 , or could not be realized at all 32,33 . It is possible here because of the weak electronic coupling between the branches (~850-900 cm −1 ) and the large charge transfer in each arm upon photoexcitation.…”
Section: Resultscontrasting
confidence: 99%
“…The most direct real-time visualization of ES-SB can be achieved by monitoring vibrational modes localized at the ends or within the D-π-A branches of these systems, using ultrafast timeresolved infrared spectroscopy (TRIR). These studies revealed how the occurrence and extent of ES-SB depend on properties of the dye itself 30,32,34,35 and of its environment [30][31][32][33] . Until now, such TRIR investigations were limited to quadrupolar molecules.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The application of the symmetry especially the spontaneous symmetry breaking has inspired many fields of physics, such as particle physics 38 , condensed matter physics 912 , physical chemistry 1316 , biological physics 17,18 and quantum information 19,20 . Mathematically, symmetry refers to that a system is invariant under some specific transformations.…”
Section: Introductionmentioning
confidence: 99%